STRATEGI PENGUATAN KARAKTER KEBANGSAAN MAHASISWA DALAM MENGHADAPI DISINFORMASI DIGITAL DAN PERUBAHAN SOSIAL BUDAYA - Widiasih, Suprapti; Akhidah, Diaz Putri (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The digital era brings serious challenges to the national character of students, especially through massive disinformation and rapid socio-cultural changes. This article aims to analyze how national character education can be strengthened in the context of the digital era, as well as identify learning strategies that are adaptive to the dynamics of the times. Using a qualitative approach based on literature study, the author reviews the theory of national character, disinformation, and globalization of values in the context of Indonesian students. The results of the study show that a strong national character must be formed through Pancasila-based contextual education, critical digital literacy, reconstruction of national narratives, and strengthening civic engagement. These findings are expected to contribute to the design of higher education policies and practices in Indonesia that are more socially and culturally relevant.